2017
DOI: 10.1007/s10068-017-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

The preservation effect of Metschnikowia pulcherrima yeast on anthracnose of postharvest mango fruits and the possible mechanism

Abstract: This study aimed to determine the effects of yeast on storage quality of 'Tainong' mango, and elucidate it's possible anti-disease mechanism. The results showed that could inhibit the changes in peel colour, fruit firmness, the contents of total soluble solids, total acid and vitamin C, and maintain the storage quality of mango fruits. An investigation of the mechanism showed that competed not only for the primary carbon source, but also for living space with. In addition, promoted the activities of defence-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Piano et al [ 74 ] found that addition of nitrates reduced or even totally suppressed the biocontrol activity of the antagonistic strains 2.33 and 4.4 against B. cinerea on apple. Similar suppression of the antagonistic effect was achieved with glucose and fructose (but not sucrose) on mango fruits [ 31 ]. Addition of these two sugars into the wounds of fruits infected with an antagonistic soil-born Metchnikowia strain and the post-harvest pathogen Colletotrichum gloeosporioides drastically increased the size of the disease lesions around the wounds.…”
Section: Antimicrobial Antagonismmentioning
confidence: 66%
See 1 more Smart Citation
“…Piano et al [ 74 ] found that addition of nitrates reduced or even totally suppressed the biocontrol activity of the antagonistic strains 2.33 and 4.4 against B. cinerea on apple. Similar suppression of the antagonistic effect was achieved with glucose and fructose (but not sucrose) on mango fruits [ 31 ]. Addition of these two sugars into the wounds of fruits infected with an antagonistic soil-born Metchnikowia strain and the post-harvest pathogen Colletotrichum gloeosporioides drastically increased the size of the disease lesions around the wounds.…”
Section: Antimicrobial Antagonismmentioning
confidence: 66%
“…Pulcherrimin-producing Metschnikowia strains are common components of the yeast communities that colonise ripening fruits, flowers (nectar), tree sap fluxes and also frequently occur in fruit juices and fermenting wine (e.g., [ 2 , 3 , 6 , 9 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]). New yeast isolates producing the characteristic maroon-red pulcherrimin halos around their colonies ( Figure 1 A) are frequently declared to belong to M. pulcherrima without taking into account that M. pulcherrima is not the only pigment-producing Metschnikowia species.…”
Section: Taxonomy Evolution and Taxonomic Identificationmentioning
confidence: 99%
“…Reduced efficiency of W. anomalus and S. cerevisiae against Pichia digitatum in orange was obtained from this mechanism [38]. Tian et al [39] reported that Metschnikowia pulcherrima could compete for nutrients under in vivo condition when glucose was added to wounds on mango fruits. Some microorganisms are capable of solubilizing insoluble essential elements such as phosphate and zinc oxide in the environment to their soluble forms, which are subsequently uptaken by plants [21].…”
Section: Introductionmentioning
confidence: 97%
“…Both species have been repeatedly isolated from grapes and other plants [22,[45][46][47][48]. Strains of M. pulcherrima have already been suggested for biocontrol of fungal diseases on apples [49], grapes [39], sweet cherries [18], strawberries [50], mango fruits [51], and even for clinical treatment of mycoses in mammals [52].…”
Section: Resultsmentioning
confidence: 99%